PERSIAPAN ASI EKSKLUSIF IBU HAMIL DI RB EVA CANDI SIDOARJO: PREPARATION OF EXCLUSIVE BREAST MILK FOR PREGNANT MOTHERS IN RB EVA, CANDI SIDOARJO - Rinata, Evi; Hamdi, Hafmi Putri Syahilda (Universitas Muhammadiyah Sidoarjo, 2015)
Preparation of exclusive breastfeeding for pregnant mother is an effort made by pregnant mother to facilitate breastfeeding exclusively, includes information search, breast care, nutritional preparation for breastfeeding, and psychological preparation for breastfeeding. Based on introduction study for pregnant in 3rd trimester, there were 62,5% haven’t prepared exclusive breastfeeding who could impact to the success of exclusive breastfeeding program. The purpose of this research was to know the description the preparation of exclusive breastfeeding at Eva’s Maternity Hospital, Candi, Sidoarjo. The type of research was used descriptive study with survey approach. The data retrieval was conducted in July to August 2015 primarily using a structured interview guide to thirty pregnant mothers in 3rd trimester. The collected data were presented in distribution table and analyzed descriptively without statistical test. The result showed almost a half, there were 46,7% of less prepare exclusive breastfeeding during pregnancy respondents, 36,7% had done enough preparation, and only 16,7% had been prepared well. This was because 30 of respondents had not tried to find information about exclusive breastfeeding, 20% had not done breast-care yet during pregnancy, 50% had not prepared the nutritions for breastfeeding, and 50% had not prepared psychologically for breastfeeding. The research was concluded there were still less preparation of exclusive breastfeeding to pregnant mother. The suggestion for health workers that they have to improve the preparation of exclusive breastfeeding to pregnant mother so that mothers can prepare for feeding and increase the success of exclusive breasfeeding program.